Conservation of core complex subunits shaped the structure and function of photosystem I in the secondary endosymbiont alga Nannochloropsis gaditana. Issue 2 (13th September 2016) - Alboresi, Alessandro; Le Quiniou, Clotilde; Yadav, Sathish K. N.; Scholz, Martin; Meneghesso, Andrea; Gerotto, Caterina; Simionato, Diana; Hippler, Michael; Boekema, Egbert J.; Croce, Roberta; Morosinotto, Tomas
Summary: Photosystem I (PSI) is a pigment protein complex catalyzing the light‐driven electron transport from plastocyanin to ferredoxin in oxygenic photosynthetic organisms. Several PSI subunits are highly conserved in cyanobacteria, algae and plants, whereas others are distributed differentially in the various organisms. Here we characterized the structural and functional properties of PSI purified from the heterokont alga Nannochloropsis gaditana, showing that it is organized as a supercomplex including a core complex and an outer antenna, as in plants and other eukaryotic algae. Differently from all known organisms, the N. gaditana PSI supercomplex contains five peripheral antenna proteins, identified by proteome analysis as type‐R light‐harvesting complexes (LHCr4‐8). Two antenna subunits are bound in a conserved position, as in PSI in plants, whereas three additional antennae are associated with the core on the other side. This peculiar antenna association correlates with the presence of PsaF/J and the absence of PsaH, G and K in the N. gaditana genome and proteome. Excitation energy transfer in the supercomplex is highly efficient, leading to a very high trapping efficiency as observed in all other PSI eukaryotes, showing that although the supramolecular organization of PSI changed during evolution, fundamental functional properties such as trapping efficiency were maintained.